Penegakan Hukum terhadap Tindak Pidana Penyebaran Konten Asusila dengan Teknik Deepfake: Studi Kasus di Polresta Malang - ramadhan gusti nugraha (Himpunan Ilmu Hukum dan Ilmu Hukum Islam, 2026)
This study examines the transformation of cybercrime from conventional pornography to artificial intelligence (AI)-based image manipulation that produces obscene content. The research aims to analyze law enforcement practices regarding the dissemination of such content within the jurisdiction of the East Java Regional Police through an empirical legal approach. The findings indicate that investigators have relied on sexual violence legislation to address previous legal gaps, while recent regulations have formally recognized electronic image manipulation as a form of sexual violence. Key challenges include difficulties in identifying anonymous perpetrators, limited digital forensic resources and low rates of victim reporting. Therefore, the modernization of investigative facilities and the enhancement of public legal awareness are essential